A Rail Network Optimization Model Designed To Model Freight Networks At A Macro Level - Luís Couto Maia (2013)
The rail freight network optimization model presented in this paper was developed as asupport tool for planning and policy decisions involved in the improvement of rail networks ona regional and national level. It is based on a strategic traffic assignment model designed tomodel macro networks with a high aggregation level, being exclusively designed for freighttraffic. The model contemplates road and rail transport modes, and considers two differenttypes of cargo: intermodal cargo, which is generally transported in containers and is easilyinterchanged between different modes at intermodal terminals; and general cargo, whichrepresents all the remaining cargo. The optimization process is based on a local searchheuristic which delivers good solutions in a reasonable computing time, with the quality ofeach network improvement solution being assessed based on the reduction of the totalgeneralized costs and CO2 emissions. This freight network optimization model is innovativein the fact that it is not limited, allowing for both the improvement of existing links as well asthe construction of new ones, and not having a limit on the number or variety of networkimprovement possibilities. Its adaptability to different conditions is emphasized when themodel is applied to a network under two different investment scenarios, by deliveringconsiderably different solutions adapted to the conditions of each scenario.Keywords: network optimization, freight transport, traffic assignment.